STUDI TENTANG KELAYAKAN AGREGAT BATU GUNUNG BUKIT MARSELA DI KABUPATEN KETAPANG SEBAGAI MATERIAL LAPIS PONDASI - Syaifullah, Asep; Sulandari, Eti; Erwan, Komala (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
West Kalimantan Province has an abundant material potential of aggregate materials, having hills, mountains and rivers that have aggregate content especially in Ketapang regency can be developed its benefits, it used as an Aggregate Base material which has a very important role in pavement. One type of road enlargement material is Aggregate Base Class A, and Class B (LPA & LPB) which have specification requirements to be fulfilled prior to spread or tamp the field, before spreading in the field the material must be tested in Laboratory to fulfill the requirements ofÂ Aggregate Foundation layer Class A, and Class B Aggregate.The determination of the maximum dry volume weight value (Î³d max) and the optimum water content (w opt) was done by compaction test in Laboratory based on SNI 1743:2008 and further to get CBR value was tested CBR Laboratorium based on SNI 1744:2012. Based on the research result, CBR Class A Aggregate Base of 91 %, maximum dry density of 2.048 kg/cm3 and optimum water content 4.20 %, Class B Class Aggregate CBR value of 84.2 %, maximum dry density 2.07 kg/cm3, moisture content optimum 6.30. It can be concluded Marsela mountain rock material can be used as pondation layer.Â Key words : Gradation, California Bearing Ratio (CBR) Class A, and Class B.